Observing : earth satellites - King-Hele, Desmond (London, United Kingdom : Macmillan Publishing Company, 1983)
The aim of this book is to provide a readable guide to the methods of tracking the 5000 or so artificial satellites in orbit about the Earth.
1. Night lights -- 2. Up and into orbit -- 3. Traffic of the sky -- 4. To see or not to see -- 5. With your own eyes -- 6. Visual arts -- 7. With camera and laser -- 8. Electronic eyes.
Includes index.
Keywords: ARTIFICIAL SATELLITES